Invasion of privacy : a novel - Reich, Christopher, 1961- (Doubleday, 2015)
On a remote, dusty road forty miles outside of Austin, Texas, FBI agent Joe Grant and a confidential informant are killed in a deadly shootout. Left to pick up the pieces is Mary Grant, Joe's young wife and mother of their two daughters. The official report places blame for the deaths on Joe's shoulders ... but the story just doesn't add up and Mary has too many troubling questions that need answers.